Setting the Holocene clock using varved lake sediments in Sweden - Zillén, Lovisa (Quaternary Sciences, Department of Geology, Lund University, 2003)
The aim of this thesis was to study annually laminated (varved) Holocene lake sediment in Sweden, their formation and their potential as chronological and palaeoecological archives. Five lakes with continuous Holocene varved lake sediment sequences in northern (Västerbotten) and west central Sweden (Värmland) were investigated. Three of these sequences were discovered during this study, which identified the climatic and environmental prerequisites for the formation of varves and, therefore, provides a tool for finding annually laminated sediments in the Swedish boreal environment. Varve chronologies, supported by other independent dating methods, i.e. radiocarbon dating, tephra isochrones and paleomagnetic secular variations were established for two sediment sequences in Värmland. These are the longest geological records with an annual resolution known to exist in Sweden. Three mid-Holocene Icelandic tephra horizons were identified within 1-cm horizons, corresponding to c. 20 years of sediment accumulation and the varve chronologies were used to assign calendar years ages to the tephra isochrones with a precision better than ± 110 varve years. Paleomagnetic secular variation curves (both directions and intensity) presented in this thesis can be used to correlate and relatively date Holocene sedimentary sequences in Northwest and Central Europe. The accuracy and precision of the method is determined by errors associated with the varve chronologies (i.e. c. 1-2%), sampling resolution (c. 50-100 years), definition uncertainties and possible remanence lock-in effects. Comparison between the paleomagnetic secular variation curves in this study and previous obtained records from Northwest Europe suggests that no significant westwards drift of the non-dipole field has occurred in this region during the majority of the Holocene. Reconstructed virtual geomagnetic pole positions for the last c. 9000 show that the Magnetic North Pole has changed its position significantly during the Holocene. Relative palaeointensities ...